(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Developmental disorders in children are still a serious problem in Indonesia. Fetal stimulation is one of the efforts to prevent developmental disorders in children. Maternal knowledge and ability are important foundations in stimulating the fetus. However, research on the level of knowledge and ability of mothers to provide fetal stimulation is still limited. This study aims to describe and identify the relationship between the knowledge and ability of pregnant women to stimulate the fetus. This study used a descriptive correlational design using a cross-sectional approach. The study sample consisted of 90 respondents selected based on inclusion criteria using a purposive sampling technique. This study used a questionnaire regarding the knowledge and ability of pregnant women to stimulate the fetus that had been tested for validity and reliability. Analysis was conducted using the chi-square test. The results showed that there was a significant relationship between the knowledge and ability of pregnant women to provide stimulation to the fetus. The results of statistical test analysis obtained a value of p = 0.001. Knowledge of pregnant women has a significant relationship with the ability of pregnant women to provide stimulation to the fetus. Keywords : Pregnant, knowledge, ability, fetal stimulation